Functional impact of an oculopharyngeal muscular dystrophy mutation in PABPN1. (25th April 2017) - García‐Castañeda, Maricela; Vega, Ana Victoria; Rodríguez, Rocío; Montiel‐Jaen, Maria Guadalupe; Cisneros, Bulmaro; Zarain‐Herzberg, Angel; Avila, Guillermo
Abstract : Key points: Mutations in the gene encoding poly(A)‐binding protein nuclear 1 (PABPN1) result in oculopharyngeal muscular dystrophy (OPMD). This disease is of late‐onset, but the underlying mechanism is unclear. Ca 2+ stimulates muscle growth and contraction and, because OPMD courses with muscle atrophy and weakness, we hypothesized that the homeostasis of Ca 2+ is altered in this disorder. C2C12 myotubes were transfected with cDNAs encoding either PABPN1 or the PABPN1‐17A OPMD mutation. Subsequently, they were investigated concerning not only excitation–contraction coupling (ECC) and intracellular levels of Ca 2+, but also differentiation stage and nuclear structure. PABPN1‐17A gave rise to: inhibition of Ca 2+ release during ECC, depletion of sarcoplasmic reticulum Ca 2+ content, reduced expression of ryanodine receptors, altered nuclear morphology and incapability to stimulate myoblast fusion. PABPN1‐17A failed to inhibit ECC in adult muscle fibres, suggesting that its effects are primarily related to muscle regeneration. Abstract: Oculopharyngeal muscular dystrophy (OPMD) is linked to mutations in the gene encoding poly(A)‐binding protein nuclear 1 (PABPN1). OPMD mutations consist of an expansion of a tract that contains 10 alanines (to 12–17). This disease courses with muscle weakness that begins in adulthood, but the underlying mechanism is unclear. In the present study, we investigated the functional effects of PABPN1 and an OPMD mutation (PABPN1‐17A) using myotubes transfected with cDNAs encoding these proteins (GFP‐tagged). PABPN1 stimulated myoblast fusion (100%), whereas PABPN1‐17A failed to mimic this effect. Additionally, the OPMD mutation markedly altered nuclear morphology; specifically, it led to nuclei with a more convoluted and ovoid shape. Although PABPN1 and PABPN1‐17A modified the expression of sarcoplasmic/endoplasmic reticulum Ca 2+ ‐ATPase and calsequestrin, the corresponding changes did not have a clear impact on [Ca 2+ ]. Interestingly, neither L‐type Ca 2+ channels, nor voltage‐gated sarcoplasmic reticulum (SR) Ca 2+ release (VGCR) was altered by PABPN1. However, PABPN1‐17A produced a selective inhibition of VGCR (50%). This effect probably arises from both lower expression of RyR1 and depletion of SR Ca 2+ . The latter, however, was not related to inhibition of store‐operated Ca 2+ entry. Both PABPN1 constructs promoted a moderated decrease in cytosolic [Ca 2+ ], which apparently results from down‐regulation of excitation‐coupled Ca 2+ entry. On the other hand, PABPN1‐17A did not alter ECC in muscle fibres, suggesting that adult muscle is less prone to developing deleterious effects. These results demonstrate that PABPN1 proteins regulate essential processes during myotube formation and support the notion that OPMD involves disruption of myogenesis, nuclear structure and homeostasis of Ca 2+ . Key points: Mutations in the gene encoding poly(A)‐binding protein nuclear 1 (PABPN1) result in oculopharyngeal muscular dystrophy (OPMD). This disease is of late‐onset, but the underlying mechanism is unclear. Ca 2+ stimulates muscle growth and contraction and, because OPMD courses with muscle atrophy and weakness, we hypothesized that the homeostasis of Ca 2+ is altered in this disorder. C2C12 myotubes were transfected with cDNAs encoding either PABPN1 or the PABPN1‐17A OPMD mutation. Subsequently, they were investigated concerning not only excitation–contraction coupling (ECC) and intracellular levels of Ca 2+, but also differentiation stage and nuclear structure. PABPN1‐17A gave rise to: inhibition of Ca 2+ release during ECC, depletion of sarcoplasmic reticulum Ca 2+ content, reduced expression of ryanodine receptors, altered nuclear morphology and incapability to stimulate myoblast fusion. PABPN1‐17A failed to inhibit ECC in adult muscle fibres, suggesting that its effects are primarily related to muscle regeneration.